Amino acids 78 and 79 of Mammalian Orthoreovirus protein μNS are necessary for stress granule localization, core protein λ2 interaction, and de novo virus replication - Carroll, Kate (2013)
At early times in Mammalian Orthoreovirus (MRV) infection, cytoplasmic inclusions termed stress granules (SGs) are formed as a component of the innate immune response, however, at later times they are no longer present despite continued immune signaling. To investigate roles of MRV proteins in SG modulation we examined non-structural protein μNS localization relative to SGs in infected and transfected cells. Using a series of mutant plasmids, we mapped necessary μNS residues for SG localization to amino acids 78 and 79. We examined the capacity of a μNS(78-79) mutant to associate with known viral protein binding partners of μNS and found that it loses association with viral core protein λ2. Finally, we show that while this mutant cannot support de novo viral replication, it is able to rescue replication following siRNA knockdown of μNS. These data suggest that μNS association with SGs, λ2, or both play roles in MRV replication.